The Influence Of Competence, Intrinsic Motivation And Rewards On Work Performance Through Satisfaction Of Employees At D.I. Yogyakarta High Prosecutor’s Office - Soekatja Adji, Agung; Chandra Kirana, Kusuma; Hadi, Syamsul (RELASI : JURNAL EKONOMI, 2024)
This research aims to analyze the influence of competence, intrinsic motivation, and rewards on work performance through employee satisfaction at D.I Yogyakarta High Prosecutor’s Office. This research used quantitative research methods using questionnaires as a data collection tool. The sample of this research consists of employees working in various sectors and levels. The collected data is analyzed using path analysis techniques to test the relationship between the variables studied. The results showed that job satisfaction also acts as a mediator between competence, intrinsic motivation, rewards, and job performance. In other words, job satisfaction acts as a link in explaining how competence, intrinsic motivation, and rewards affect job performance. But from the results, it can be seen that intrinsic motivation and rewards do not affect job performance through satisfaction while competence affects job performance through satisfaction. The implication of this research is the importance of the DI Yogyakarta High Prosecutor’s Office to pay attention to competency factors in improving employee work performance. Fair training and competency development can increase employee job satisfaction, which in turn will have a positive impact on their job performance. Although intrinsic motivation and rewards are not proven to have an effect, they still need to be considered and understood in a broader context to ascertain other factors that can affect employee performance.